Simon's Favourite Factoring Technique again!
The three equations can be written as
(1+x) (1+y) = (1+z)..................................1
(1+y) (1+z) = (1+x).................................2
(1+z) (1+x) = (1+y).................................3
Multiplying the three equations we get
A2 = A where A = (1+x) (1+y) (1+z)
Hence A = 0 or A = 1
If A = 0, then we have x=y=z= -1
If A = 1, then we have
first we see that each of x,y and z can be 0 or -2
Obviously x = y = z = 0 is one solution
The other solutions are permutations of (0,-2,-2)